Effects of Ecologically Relevant Concentrations of Cadmium on the Microbiota, Short-Chain Fatty Acids, and FFAR2 Expression in Zebrafish - Jian Yang; Junyi Li; Xiaoshun Zhang; Qin Zhou; Junyi Wang; Qingsong Chen; Xiaojing Meng; Yuan Xia (Metabolites, 2023)
Exposure to cadmium (Cd) can affect neurodevelopment and results in increased potential of developing neurodegenerative diseases during the early developmental stage of organisms, but the mechanisms through which exposure to environmentally relevant concentrations of Cd lead to developmental neurotoxicity remain unclear. Although we know that microbial community fixations overlap with the neurodevelopmental window during early development and that Cd-induced neurodevelopmental toxicity may be related to the disruption of microorganisms during early development, information on the effects of exposure to environmentally relevant Cd concentrations on gut microbiota disruption and neurodevelopment is scarce. Therefore, we established a model of zebrafish exposed to Cd (5 µg/L) to observe the changes in the gut microbiota, SCFAs, and free fatty acid receptor 2 (FFAR2) in zebrafish larvae exposed to Cd for 7 days. Our results indicated that there were significant changes in the gut microbial composition due to the exposure to Cd in zebrafish larvae. At the genus level, there were decreases in the relative abundances of Phascolarctobacterium, Candidatus Saccharimonas, and Blautia in the Cd group. Our analysis revealed that the acetic acid concentration was decreased (p > 0.05) while the isobutyric acid concentration was increased (p < 0.05). Further correlation analysis indicated a positive correlation between the content of acetic acid and the relative abundances of Phascolarctobacterium and Candidatus Saccharimonas (R = 0.842, p < 0.01; R = 0.767, p < 0.01), and a negative correlation between that of isobutyric acid and the relative abundance of Blautia glucerasea (R = −0.673, p < 0.05). FFAR2 needs to be activated by SCFAs to exert physiological effects, and acetic acid is its main ligand. The FFAR2 expression and the acetic acid concentration were decreased in the Cd group. We speculate that FFAR2 may be implicated in the regulatory mechanism of the gut–brain axis in Cd-induced neurodevelopmental toxicity.